Characterization Of Myocardial Dysfunction in Patients with Arterial Hypertension - Rajabova N.T; Kilicheva T.A (Peerian Journals Publishing, 2024)
The article characterizes early myocardial dysfunction (DM) in patients with threshold arterial hypertension (AH) and 1st degree AH. The technique of high-amplitude reflected motion signals (VOSD) has a higher sensitivity for detecting initial dysfunction in the left ventricular myocardium compared with traditional echodoppler parameters. WOSD allows to determine the parameters of diagnostic significance for Ea(c), Aa(c), Ea(c)/Aa(c), Ea(c) and Aa(c) in the separation of healthy individuals and 1st degree AH patients with already appeared minimal left ventricular diastolic dysfunction.
Keywords: myocardial dysfunction; arterial hypertension; systolic blood pressure